2017
DOI: 10.3390/e19110599
|View full text |Cite
|
Sign up to set email alerts
|

Sparse Coding Algorithm with Negentropy and Weighted ℓ1-Norm for Signal Reconstruction

Abstract: Abstract:Compressive sensing theory has attracted widespread attention in recent years and sparse signal reconstruction has been widely used in signal processing and communication. This paper addresses the problem of sparse signal recovery especially with non-Gaussian noise. The main contribution of this paper is the proposal of an algorithm where the negentropy and reweighted schemes represent the core of an approach to the solution of the problem. The signal reconstruction problem is formalized as a constrai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…We propose to exploit the negentropy of measurement error, , as the objective function as a new model. According to information theory, among all random variables with equal variance, the entropy of Gaussian variables is the largest [ 23 ]. Obviously, entropy can measure the Gaussian property of a variable, so negentropy can be used to measure its non-Gaussian property; the larger the negentropy is, the stronger the non-Gaussian variable is.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…We propose to exploit the negentropy of measurement error, , as the objective function as a new model. According to information theory, among all random variables with equal variance, the entropy of Gaussian variables is the largest [ 23 ]. Obviously, entropy can measure the Gaussian property of a variable, so negentropy can be used to measure its non-Gaussian property; the larger the negentropy is, the stronger the non-Gaussian variable is.…”
Section: Methodsmentioning
confidence: 99%
“…To achieve more accurate recovery, research focusing on the -LA minimization problem was reported in [ 22 ]. Meanwhile, it was demonstrated in [ 23 ] that the negentropy of measurement error can achieve good recovery performance with non-Gaussian noise. Whilst the focus of [ 23 ] is to present a novel method of error measurement, it also suggests an optimized algorithm that combines forward-backward splitting to solve the robust CS formulation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…They achieve better performance than the method in [10] with the same number of nonzero taps. Furthermore, for the pursuit of both sparse promotion and improved accuracy, the sparse signals reconstruction algorithms inspired by l 1 and weighted l 1 regularization schemes are proposed in [17,18]; the joint smoothed l 0 norm algorithm for direction-of-arrival estimation in MIMO radar is proposed in [19]. …”
Section: Introductionmentioning
confidence: 99%